NASIONALISME MUDA PADA KOMUNITAS K-POPERS MELALUI ANALISIS SIKAP DAN ETIKA MORAL WARGA NEGARA INDONESIA - Hasanah, Rizky; Dewantara, Jagad Aditya (Academy of Education Journal, 2023)
K-Pop or Korean Pop is a South Korean entertainment industry that is being liked by many people in the world. K-Pop culture is much liked by young people. Korean Pop is a part of the Korean Wave, namely in the music industry. The purpose of this study is to analyze the attitude of nationalism towards Pancasila that is developing among young people, especially Pontianak K-Popers and to analyze the shift in attitudes and moral ethics of young people in the K-Popers community due to the influence of foreign cultures such as K-Pop culture. The type of research used is descriptive qualitative. The number of informants was 16 people from various K-Popers communities in Pontianak with an age range of 17-22 years. The results of the study show that the Pontianak K-Popers community remains nationalist, even though it has lost its local identity by retaining its citizenship status as an Indonesian citizen and continuing to defend the Indonesian state if someone insults and demeans the dignity of the Indonesian nation. K-Popers also continue to apply Pancasila values ​​in their lives, but there are several attitudes that are contrary to Pancasila values. For this reason, Indonesian people must be able to filter foreign cultures that enter Indonesia by racing on Pancasila values.